The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jcm10163592
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Rater Reliability of Magnetic Resonance Imaging in Comparison to Computed Tomography and Wrist Arthroscopy in SLAC and SNAC Wrist

Abstract: The aim of the study was to assess the inter-rater reliability of magnetic resonance imaging (MRI) in comparison to computed tomography (CT) and wrist arthroscopy in patients with scapholunate (SLAC) or scaphoid non-union advanced collapse (SNAC) as well as to evaluate a grading score of cartilage lesions. A total of 42 patients (36 male, 6 female) at a mean age of 45 years (range: 19–65 years) with a SLAC or SNAC wrist who had a preoperative MRI and CT scan as well as underwent arthroscopy of the wrist betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A study by Ochman et al (2017) confirmed that the 3.0 T MRI examination with a wrist coil is promising for cartilage assessment and is a much more accurate diagnosis tool compared with the 1.5 T MRI examination. Terzis et al (2021) also demonstrated a strong correlation between 3.0 T MRI and wrist arthroscopy in the assessment of cartilage lesions. They concluded that MRI is a useful diagnostic tool for cartilage assessment in patients with SNAC or SLAC wrist.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A study by Ochman et al (2017) confirmed that the 3.0 T MRI examination with a wrist coil is promising for cartilage assessment and is a much more accurate diagnosis tool compared with the 1.5 T MRI examination. Terzis et al (2021) also demonstrated a strong correlation between 3.0 T MRI and wrist arthroscopy in the assessment of cartilage lesions. They concluded that MRI is a useful diagnostic tool for cartilage assessment in patients with SNAC or SLAC wrist.…”
Section: Discussionmentioning
confidence: 68%
“…Although arthroscopy remains the gold standard for detecting cartilaginous lesions, magnetic resonance imaging (MRI) is a useful diagnostic tool for cartilaginous lesions of the wrist (Terzis et al., 2021). As treatment can be influenced by the SNAC stage, it is important to assess if the distribution of cartilage damage associated with SNAC follows the same pattern.…”
Section: Introductionmentioning
confidence: 99%
“…For all snail genera, snail abundance reported by the CSs were positively correlated with those obtained by the expert. However, the correlation values were lower than those reported in other studies about intercoder reliability [68][69][70]. Nevertheless, most of these studies focus on medical diagnosis, which involves fewer categories of classification, and therefore fewer opportunities for disagreement.…”
Section: Can Citizens Reliably Monitor Snail Abundance In Given Site/...mentioning
confidence: 62%